2009
DOI: 10.1111/j.1949-3606.2009.tb01104.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Digital Libraries in Egyptian Higher Education

Abstract: Exploring the students' information, communication technology (ICT) profile and how it may affect their attitudes towards the Egyptian university digital library (EUDL) and the role of the digital library in the educational and research activities in faculties of nursing and education in Egypt is the main concern of this study. A questionnaire was distributed to students in the faculties of Nursing and Education at five Egyptian universities. A total of 4008 responses have been received and analyzed. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In a survey of 194 undergraduate and post-graduate students 89% stated that they used computer-based literature searches at least once per month to either prepare presentations (90.2%), carry out research (65%), or to research patient-related problems (60.3%) [12]. Following-up on this trend, in Egypt a digital library was made available to nursing students, and Taie explored the role of these libraries on student awareness, student knowledge and attitudes toward them [13]. …”
Section: Introductionmentioning
confidence: 99%
“…In a survey of 194 undergraduate and post-graduate students 89% stated that they used computer-based literature searches at least once per month to either prepare presentations (90.2%), carry out research (65%), or to research patient-related problems (60.3%) [12]. Following-up on this trend, in Egypt a digital library was made available to nursing students, and Taie explored the role of these libraries on student awareness, student knowledge and attitudes toward them [13]. …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, librarians must advertise the library's electronic resources to students in order for them to know they exist, what they are and how to use them. Taie and Mohamed (2009) used 4,000 student responses to examine user perceptions of a digital library collection in an Egyptian academic library. The study found that nursing students were the most frequent users of the digital library.…”
Section: Review Of Previous Studiesmentioning
confidence: 99%